(untitled) (Revista de Ciências Agroveterinárias, 2008)
Leaf cutting ants of the genus Acromyrmex are social insects found in most Brazilian agriculture systems. The continuous change in flora composition caused by intensive agricultural systems increased Acromyrmex leaf-cutting activity, causing severe damages to crops. This work was carried out in order to study the behavior of leaf-cutting ants Acromyrmex spp. in the high lands of Santa Catarina State, Brazil. The research was performed during 2007, on ant colonies located in city of Lages. The experiment was carried out during a period of 10 months. Data were collected each two hours of a day per month. The total number of leafcutting ants, the number of foraging ants in a period of one minute and the kind of foraged plant were assessed. Results showed that ant moving and foraging activity were higher during the summer season months. The highest foraging activity during the summer months was observed at night, whereas in the winter time leafcutting ants showed higher activity in the morning. Leaf-cutting ants visited a lower number of vegetable species in the winter than in the summer. The species Rumex obtusifolius was the most visited plant by Acromyrmex spp. with 90% of total foraging frequency, whereas Oxalis spp. was the less visited species.